Did you choose appropriate mouthwash for managing chemoradiotherapy-induced oral mucositis? The therapeutic effect compared by a Bayesian network meta-analysis. - Wang, Xue; Zeng, Li; Feng, Xue; Zhao, Na; Feng, Na; Du, Xin (Frontiers in Oral Health, 2023)
Background: Oral mucositis (OM) is one of the most common adverse effects of radiotherapy and chemotherapy. It greatly affects the patients' quality of life and hinders cancer treatment implementation. Treating OM with mouthwash is a widely used strategy that can effectively relieve symptoms and promote healing. However, the wide mouthwash selection confuses clinicians. This Bayesian network meta-analysis aimed to compare the effects of various mouthwash types used to treat OM and provide high-level evidence-based recommendations for OM treatment. Methods: Database search included PubMed, Embase, Cochrane Library, and Web of Science from inception to April 21, 2022. The primary outcome was OM score improvement following the World Health Organization grades. The randomized controlled trial (RCT) bias risk assessment tool provided in the Cochrane Handbook assessed the studies' risk of bias. We performed pairwise and Bayesian network meta-analysis with random effects following the PRISMA guideline. Results: The study included 13 RCTs with 570 patients. Pairwise comparisons showed that povidone-iodine was more effective than chlorhexidine (weighted mean difference [WMD], –2.64; 95% confidence interval [CI], –2.72 to –2.56) but inferior to granulocyte-macrophage colony-stimulating factor (GM-CSF; WMD, 0.20; 95% CI, 0.06–0.34) after one week of mouthwash treatment. Vitamin E (WMD, –0.94; 95% CI, –1.03 to –0.85), natural drugs (WMD, –0.93; 95% CI, –1.46 to –0.40), and phenytoin (WMD, –0.38; 95% CI, –0.59 to –0.17) exhibited better therapeutic effects than a placebo after three weeks of treatment. Bayesian network meta-analysis showed that povidone-iodine was superior to chlorhexidine in treating OM (WMD, 2.63; 95% CI, 0.20–5.01). Other mouthwashes showed no significant differences. Rank probability indicated that the best OM therapeutic mouthwashes were GM-CSF (54%), vitamin E (24%), and natural drugs (43%) after one, two, and three weeks of treatment, respectively. Conclusion: GM-CSF was the most effective mouthwash type for OM treatment. When considering the cost and effectiveness, povidone-iodine and sodium bicarbonate might be the most advantageous. Furthermore, natural drugs have the same potential in treating OM. Safety and acceptability are their most outstanding characteristic.